Survey on the quality of life of pharmaceutical professionals of drugstore (Research, Society and Development, 2021)
Objective: This study has the objective of assessing the quality of life among pharmacists, especially in the drug network. Methodology: Or instrument adapted from WHOQOL, using 5 domains (biological, psychological, level of independence, social relations and work-life), establishing scores for the domains and for the quality of life. Included in the list are not 21 pharmacists of both genders, of varying degrees and time of skill, who work in a drug store from network functions of Pharmaceutical Managers (GF) and Technical Responsible (RT). Results: There was a predominance of women, RT, between 20-40 years old, who had more than two domains for which they were classified as good to very good. In the meantime, no domain III (level of independence), 20 pharmacists demonstrated a reduced level and scored less than 5 and only 1st note was 5. For the other domains, the pharmacist numbers with a note lower than 5.0 (classified as bad) was: biological ID-4, psychological ID-2; DIV social relationships-4 e DV housing work- 2. Meanwhile, due to the low scores on DIII, 8 pharmaceutics were classified as low quality of life. It was realized also that the instrument allows to track some health problems, relationships, labor problems, as well as an endorsement of the quality of life. Conclusion Despite the small number of participants, the results should not be disregarded. They can indicate that many pharmaceuticals may be facing serious problems of health, relationships and non-work. In this context, it is important that new studies are carried out to assess the quality of life and trace two possible problems faced in the class.